The Evolution of Distributed Systems: A Systematic Literature Review from Centralized Computing to Cloud, Edge, and Fog Paradigms: Evolusi Sistem Terdistribusi: Tinjauan Literatur Sistematis dari Komputasi Terpusat hingga Paradigma Cloud, Edge, dan Fog - Nur Fitriyah Ramadhani; Rahmaniar Rahmaniar (WITECH: Jurnal Teknologi Rekayasa Komputer dan Jaringan, 2026)
Distributed systems form a fundamental foundation for many modern digital services, including Cloud Computing, the Internet of Things (IoT), and data-driven intelligent applications. Their development originated from Centralized Computing models based on mainframe systems and gradually evolved into distributed architectures as networking technologies and hardware capabilities advanced. This study aims to examine the evolution of distributed systems and identify emerging trends and challenges using a Systematic Literature Review (SLR) approach based on selected textbooks and scientific publications. The results indicate that distributed systems have progressed toward modern architectures integrating Cloud, Edge, and Fog Computing within a distributed Computing Continuum. However, several challenges remain significant, including data consistency, heterogeneous resource management, security, and scalability in large-scale distributed infrastructures.Top of Form